2008
DOI: 10.1016/j.neuroimage.2008.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Warm pleasant feelings in the brain

Abstract: Warm and cold stimuli have affective components such as feeling pleasant or unpleasant, and these components may have survival value, for approach to warmth and avoidance of cold may be reinforcers or goals for action built into us during evolution to direct our behaviour to stimuli that are appropriate for survival. Understanding the brain processing that underlies these prototypical reinforcers provides a direct approach to understanding the brain mechanisms of emotion. In an fMRI investigation in humans, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
161
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(174 citation statements)
references
References 52 publications
9
161
1
Order By: Relevance
“…74). In addition, the OFC was sensitive to visual sex (with effect sizes similar to those in SI), in agreement with the affective valuation often associated with this region (11)(12)(13). Previous models have associated the medial OFC with the monitoring and memory of the reward value of reinforcers (75), and the medial orbital gyrus specifically with the positive value of erotic as opposed to monetary reinforcers (76).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…74). In addition, the OFC was sensitive to visual sex (with effect sizes similar to those in SI), in agreement with the affective valuation often associated with this region (11)(12)(13). Previous models have associated the medial OFC with the monitoring and memory of the reward value of reinforcers (75), and the medial orbital gyrus specifically with the positive value of erotic as opposed to monetary reinforcers (76).…”
Section: Discussionsupporting
confidence: 81%
“…Prevailing models of how the brain processes the sensory and affective properties of gentle touch have drawn predominantly on experiments that used inanimate objects with varying textures, rather than interpersonal touch (2,3), or from the known neural organization of unmyelinated, Ctactile (CT) fibers in hairy skin (4-7), which respond specifically to light touch (8) and project to and activate the insula, but project to and inhibit the primary somatosensory cortex (SI) (9,10). Differences in brain activation in the insula, anterior cingulate cortex (ACC), and orbitofrontal cortex (OFC) have been found according to stimulus type (e.g., a wooden rod vs. a velvet cloth) (11) and subjective ratings of emotion (12,13). Thus, previous work has shown that SI primarily discriminates sensory properties (e.g., location, pressure, texture), whereas the insula, together with the ACC and the OFC, primarily discriminate affective/emotional properties (i.e., perceived pleasantness) (7,11,14,15).…”
mentioning
confidence: 99%
“…Stroking touch hyperhedonia and analgesia responses both correlated with increases in the pgACC. In addition to its role in pain modulation and placebo responses, this region is paramount for emotion appraisal and valuation processing (27), and is activated by pleasant tactile stimuli, such as warmth (37), massage (38), and soft gentle strokes to the skin (39).…”
Section: Common Emotion Appraisal Circuitry Mediated Behavioral and Boldmentioning
confidence: 99%
“…The CC is implicated in a diverse array of functions, such as emotion (George et al., 1995; Kross, Davidson, Weber, & Ochsner, 2009; Liotti et al., 2000; Rogers et al., 2004; Rolls, Grabenhorst, & Parris, 2008; Walter et al., 2008, 2009), movement (Beckmann, Johansen‐Berg, & Rushworth, 2009; Paus, 2001; Picard & Strick, 1996, 2001), self‐relevant assessment (Kelley et al., 2002; Vogt, Vogt, & Laureys, 2006), cognition (Luo et al., 2007; Pourtois et al., 2010; Sohn, Albert, Jung, Carter, & Anderson, 2007; Ursu, Clark, Aizenstein, Stenger, & Carter, 2009), memory (Maguire, 2001), visuospatial orientation (Vogt et al., 2006), navigation, imagination, and planning for the future (Vann, Aggleton, & Maguire, 2009). …”
Section: Introductionmentioning
confidence: 99%